Implementasi Penggunaan QR Code sebagai Media Pembelajaran Pendidikan Agama Islam pada Siswa Kelas XII Nur Al-Jadid Waru Sidoarjo - Sholicha, Nikmatus; Rohmah, Nadia Wulidar; H, Rizky Fahdurrosi A. N.; Mawardi, Munif; Fatkhurrozi, Moch (Lembaga Intelektual Muda (LIM) Maluku, 2026)
Advances in information technology have a significant impact on the world of education, including Islamic Religious Education (PAI) learning. The use of technology is necessary to avoid monotonous learning, so teachers are required to develop innovative learning media, one of which is through the use of QR Codes. This study aims to determine the impact of using QR Code media in PAI learning at MA Nur Al-Jadid Waru Sidoarjo. This study uses a qualitative descriptive approach with 16 grade XII students as subjects. Data were collected through observation and literature studies, then analyzed using an interactive analysis model that includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the use of QR Code media has a positive impact on PAI learning, marked by increased student interest and activeness, ease of independent material access, and a better understanding of abstract PAI material. QR Code media is considered effective and relevant to the characteristics of students in the digital era.